Os cartões fotográficos oitocentistas na construção da identidade social do retratado e da identidade profissional do fotógrafo - Luiz Henrique Vieira (2019)
The proposal of this work is to investigate, through the perspective of the social history of culture, the photographic cards - denomination given to certain portraits produced in studios, between 1854 and 1920, that followed certain aesthetic standards, involv-ing the appreciation of both the pose and clothing (appearance issues), and the setting of the portrayed in scenarios of neoclassical inspiration. These cards were composed by the portrait (influenced by canons of the pictorial portraiture) and by information (textual and imagery) about the photographer and his studio. The research was carried out from the hypothesis that these portraits had served as a tool in the construction and dissemination of the social identity of the portrayed (individuals representing the emerging social classes in that length of time), in the same way that served as a medi-um for the construction and disclosure of the professional identity of the photogra-pher, considering the recent emergence of this craft.